GESTATIONAL TROPHOBLASTIC NEOPLASIA (GTN) PATIENT PROFILE AT SANGLAH HOSPITAL DENPASAR IN JANUARY 2012-DECEMBER 2014 - Ketut Suwiyoga, I Gde Sastra Winata, (E-Journal Obstetric & Gynecology Udayana, 2015)
Gestational Trophoblastic Neoplasia (GTN) was a malignant tumor from Chorionic Villi, especially from trophoblastic cell in pregnancy, mole or non hydadityform mole. The GTN incidence was varies in the world and tend to increasing in every year especially in developing countries. GTN was a malignant tumor that has an unique characteristic, such as: frequently in young women, low parity, has specific tumor marker, beta-hCG that has prognostic value, and was be the only malignancy that can be treated thoroughly. In social-economic GTN was a malignancy that became a burden on health services because of the high incidence, high cost therapy, and became poor prognosis if not in the good therapy. This article will explain about GTT patient profile at Sanglah Hospital in 2012-2014. This research was an descriptive retrospective research at Obstetric and Gynecologic Polyclinic, Gynecologic ward and Medical Record Installation at Sanglah Hospital in November until December 2014. During the research periode that was 19 GTN cases. Number of incident of GTN mostly in 31-35 years patient, about 36,8% (7 cases) with 2 parity, 36,8% (7 cases), with previous pregnancy with hydadityform mole, about 68,4%. Interval between pregnancy with GTN diagnose mostly was more than 100.000mIU/ml, about 57,9%. About 26,3% case metastasized, 80% in lung and 20% in bone. About 68,4% Histopathology type was hydadityform mole and 31,6 % was choriocarcinoma. Most of the GTN cas found in first stage, about 63,2%, in stage II, III and IV is 10,5%, 21,1% and 5,3%. Chemotherapy type that given to the patient, Methotrexate (MTX) 73,7%, combination chemptheraphy, Actinomycin D (ACD), Chlorambucil (MAC) and Etoposide, MTX, ACD, Cyclophosphamide, Oncovine (EMACO) WAS 10,5% AND 15,8%. Key word : Gestational Trophoblastic Neoplasia (GTN) profile